1989
DOI: 10.1152/jappl.1989.67.5.1997
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of human endothelial monolayers: effect of vasoactive agonists and cAMP

Abstract: Permeability coefficients of human umbilical vein endothelial cell monolayers cultured on polycarbonate filters were determined by monitoring transendothelial albumin transport. Permeability was determined as a function of time in culture and in the presence of vasoactive agonists. Permeability decreased with increasing time in culture. All agonist experiments were performed with 15-day cultures because this time point best modeled the in vivo permeability barrier function. Permeability of endothelial monolaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
55
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 0 publications
9
55
1
Order By: Relevance
“…Db-cAMP has been demonstrated to attenuate lung injury from a number of injurious stimuli [17][18][19][20][21]. However, the mechanism of protection in these instances is not known, although there is evidence that in some in vivo models it may exert a beneficial response by reducing pulmonary vascular pressures [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Db-cAMP has been demonstrated to attenuate lung injury from a number of injurious stimuli [17][18][19][20][21]. However, the mechanism of protection in these instances is not known, although there is evidence that in some in vivo models it may exert a beneficial response by reducing pulmonary vascular pressures [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of protection in these instances is not known, although there is evidence that in some in vivo models it may exert a beneficial response by reducing pulmonary vascular pressures [19,20]. However, there is also evidence that this protection may be related to decreasing endothelial permeability [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cAMP-dependent protein kinase (PKA) has significant and profound protective actions against increases in endothelial permeability. We and others (4,10,32,42,43) have shown that the ubiquitous cellular messenger cAMP prevents increases in endothelial permeability in response to a wide range of inflammatory mediators, including oxidants. Although growing evidence indicates that cAMP activates both PKA-dependent and -independent actions (8,11,26), our recent observations show that protective actions of cAMP against barrier dysfunction are likely mediated predominantly through PKA-dependent signaling mechanisms (32,43).…”
mentioning
confidence: 89%
“…Traditionally, the permeability of human endothelium has been examined in planar cell cultures in vitro (12). These cultures lack physiologically relevant shear stress, and the permeability coefficients are averaged over large areas and long times.…”
Section: Introductionmentioning
confidence: 99%